As pedagogias do Movimento Negro no Rio de Janeiro e Santa Catarina (1970-2000): implicações teóricas e políticas para a educação brasileira - Lima, Ivan Costa (2009)
The present work is a deepening, initiated in the master course in Education, on thinking and on the pedagogical work of the Movimento Negro (MN) entities in Brazil, that had nominated as pedagogia the models that guide its projects of education for Brazil. This subject reveals excellent in the measure where I long for to surpass the unfamiliarity in the society and the history of the Education of pedagogical proposals developed by the Black Movement. I investigate the Pedagogia Multiracial, developed in Rio De Janeiro, for Maria Jose Lopes da Silva and a group of educators, in the decade of 80, of century XX. As well as its unfolding, in century XXI, the elaboration of the Pedagogia Multiracial and Popular, in the state of Santa Catarina, for the Nucleus of Estudos Negros (NEN), entity of the MN of the capital. The research has as referencial theoretician-metodológico a partner-historical perspective, considering the social citizens, its origins and relations, that if had established in its trajectories. This historical vision will be combined with the use of thematic Verbal History, as possibility to deepen the meanings of the cultural universe and politician of integrant of this movement and its consequences in the educational politics in Brazil. By means of the this proposal of systematization of the pedagogias developed for the MN, I look for to contribute in the advance of the debate on the racial relations, the culture and history of the black population, that if verify in the scope of the Brazilian Education contemporary and that they continue to produce exclusion and inaqualities of the most varied forms